KOMUNIKASI DAKWAH IMAM AL-GHAZALI DALAM KITAB IḤYĀ ‘ULUMIDDĪN - Pia Khoirotun Nisa (Wardah, 2018)
Abstract: Dakwah communication of Imam al-Ghazali in his book Ihya Ulumuddin explains about the understanding of dakwah briefly and clearly. The book stresses to internalization process, diffusion, institutionalization and transformation of Islamic teaching that involves some aspects for realizing good life, safety and light in the world and in the world after here. In describing this subject, namely the preaching paradigm of Imam al-Ghazali, the author will share it in several subtopics. As one of the scholars who have long been devoted to the missionary arena. Moving on from the analysis of the study of the book Iḥyā` 'Ulūmiddīn, the author will share the discussion in this chapter as follows: Al-Ghazali's idea of Da'wah and its Concepts. Keywords: Dakwah Communication, Islamic Teaching